Risk Factors for Anemia in Pregnant Women at Hj Ida Maternity Clinic, Bogor Regency, 2022 - Atik Kridawati; Yenni Ariestanti; yelaruci (Jurnal Ragam Pengabdian, 2026)
Anemia in pregnant women is a maternal health problem influenced by various risk factors, making it an important focus in nursing and midwifery studies. Understanding these factors is necessary to support prevention efforts and improve health. This study aims to determine the risk factors for anemia in pregnant women. This is a descriptive analytical study using a cross-sectional approach. The sample consisted of 145 pregnant women. Data were collected using questionnaires, medical records or KIA books, and upper arm circumference measurements. Data analysis was performed using logistic regression. Knowledge, parity, chronic energy deficiency, dietary patterns, and iron supplement adherence were associated with anemia (p < 0.05), while education, age, and occupation were not (p > 0.05). Furthermore, parity, dietary patterns, and iron supplement adherence were simultaneously associated with anemia (p < 0.05), with dietary patterns being the dominant variable. There is a relationship between knowledge, parity, chronic energy deficiency, diet, and FE intake compliance with the incidence of anemia, while education, age, and occupation show no relationship. Furthermore, there is a simultaneous relationship between parity, diet, and FE intake compliance with the incidence of anemia, and diet is the dominant variable.